Overview study of the use of several weighing instruments for static determination of vehicle mass in Germany. (December 2021) - Foyer, Gisa; Schulz, Karsten
Abstract: This paper focuses on combined weighing, a method of vehicle mass determination using non-automatic weighing instruments that allows the mass of very long vehicles to be determined. However, because almost no studies on this topic exist, it is uncertain whether this method should be used by law enforcement. In the following paper, a large data set is analysed to determine influences on combined weighing.